DIGITAL TOOLS IN EDUCATIONAL POLICY AND ADMINISTRATION FOR SPORTS (REMUNOM, 2025)
This study represents an in-depth, bibliographically informed analysis of sources, within the context of an active educational development addressing football and its biases. Documentary and bibliographic research was conducted across various digital media platforms, such as social media (Twitter, currently X, Facebook, and Instagram), as well as databases such as Google Scholar (GA), Web of Science (WoS), and Scopus. Content analysis was conducted using Bardin's (1979, 2011) principles, including bibliographic analysis, providing a robust theoretical and methodological basis for the analysis of texts, documents, and other data sources. Conflict resolution. By combining punitive and educational measures, it is possible to create a safer and more harmonious future in stadiums, reclaiming football as an element of social unity and cultural spectacle. Information technologies and connectivity play a crucial role in shaping a more informed and interconnected society, becoming essential in promoting responsible behavior among fans. The study is expected to contribute to a safer and more conscious sports environment by integrating new educational technologies into prevention and awareness strategies.